2021
DOI: 10.3390/molecules26123585
|View full text |Cite
|
Sign up to set email alerts
|

Santamarine Shows Anti-Photoaging Properties via Inhibition of MAPK/AP-1 and Stimulation of TGF-β/Smad Signaling in UVA-Irradiated HDFs

Abstract: Chronic UVA exposure results in elevated reactive oxygen species in skin which leads to photoaging characterized as upregulated matrix metalloproteinase (MMP)-1 and loss of collagen. Therefore, natural antioxidants are hailed as promising agents to be utilized against photoaging. In the current study, reynosin and santamarine, two known sesquiterpene lactones isolated from Artemisia scoparia, were analyzed for their anti-photoaging properties in UVA-irradiated human dermal fibroblasts (HDFs). Results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Santamarine, a sesquiterpene lactone, isolated from sunflower family provided anti-photoaging effects via suppression of UVA (8 J/cm 2 )-induced MAPK/AP-1 pathways involved in upregulation of MMPs and via promotion of TGF-β/Smad-mediated collagen production in HDFs. Furthermore, santamarine treatment led to a significant restoration of UVA-mediated downregulation of Nrf2-dependent antioxidant defenses including SOD-1 and HO-1 at the mRNA and protein levels ( Oh et al, 2021 ). Zerumbone (ZER), a natural sesquiterpene, from Zingiber zerumbet (L.) Roscoe ex Sm.…”
Section: Introductionmentioning
confidence: 99%
“…Santamarine, a sesquiterpene lactone, isolated from sunflower family provided anti-photoaging effects via suppression of UVA (8 J/cm 2 )-induced MAPK/AP-1 pathways involved in upregulation of MMPs and via promotion of TGF-β/Smad-mediated collagen production in HDFs. Furthermore, santamarine treatment led to a significant restoration of UVA-mediated downregulation of Nrf2-dependent antioxidant defenses including SOD-1 and HO-1 at the mRNA and protein levels ( Oh et al, 2021 ). Zerumbone (ZER), a natural sesquiterpene, from Zingiber zerumbet (L.) Roscoe ex Sm.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that monoterpenes and sesquiterpenes such as myrcene, (–)-loliolide, camphor, and santamarine exhibit anti-skin damage, antioxidant, and anti-inflammatory effects by modulating signaling pathways including MAPKs, NF-κB, phosphoinositide 3-kinase/protein kinase B (PI3K/AKT), extracellular signal-kinase (ERK), transforming growth factor-β/suppressor of mothers against decapentaplegic (TGF-β/Smad), AP-1, and Nrf2/ARE in HDFs. 34–38 Moreover, several monoterpenes and sesquiterpenes increase collagen expression and decrease MMP-1 expression. 31–38…”
Section: Resultsmentioning
confidence: 99%
“…UV irradiation induces collagen degradation by causing overexpression of MMP-1. Therefore, reducing MMP-1 levels is a key factor in preventing UVA-induced photoaging [22]. We investigated the effects of Q-3-GR on MMP-1 production and protein expression using ELISA and western blotting.…”
Section: Effects Of Q-3-gr On Mmp-1 Expression In Uva-irradiated Hdfn...mentioning
confidence: 99%